Motivational Mechanisms of Demonstration of Professional Competences in a Situation of Uncertainty - Korchemnyj, Petr A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The research paper establishes that the efficient resolution of a situation of uncertainty is achieved due to the motivational mechanisms for the manifestation of professional competencies. The psychological essence of the condition of uncertainty, the role of needs, intentions and professional goals in the restructuring of energy in the mental apparatus of a person, the place of motive as a conscious impetus of a person to specific actions are revealed. The author proposed the concept of the relationship of psycho-physiological and motivational mechanisms for the actualization of professional competencies in a situation of unexpected changes in the professional goals and objectives of the activity. The topicality of the work is due to the need to study the effect of motivation to act on the manifestation of professional competencies in a situation of uncertainty. An important goal of the research paper is assessed - a theoretical-psychological analysis of the motivational mechanisms for the expression of professional competencies of a subject of activity internally motivated for success in an unexpected professional situation, taking into account his personal, professional skills. The theoretical significance of our work is in the theoretical-methodological substantiation of the motivational model for the manifestation of the abilities of an extreme profession specialist’s personality to apply professional competence in the conditions of uncertainty. It has been proved that the motivational factor of actualization of professional competencies in a situation of risk is fundamental in deciding to cope with unforeseen difficulties.